Leadership for Transformational Learning: A Developmental Approach to Supporting Leaders' Thinking and Practice. (August 2014) - Drago-Severson, Ellie; Blum-DeStefano, Jessica
Given the complexity of contemporary leadership, scholars and practitioners seek to improve preparation programs so that school leaders can more effectively support adult development. This article describes longitudinal research investigating how a university course on leadership for adult development ( Leadership for Transformational Learning [LTL]) influenced graduates' conceptions of leadership immediately after the course and years later. This article describes (a) course goals, structures, and curricula; (b) changes in thinking that leaders attributed to LTL; and (c) course ideas and practices that leaders named as essential to their current thinking and work. This investigation offers insight into how university courses can support leaders' internal growth.